The Importance of Knowledge Management for the Innovativeness of the Public Sector - Vaitkevičius, Viktoras (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English] One of the most relevant topics discussed in the global political arena is the economic development and the competitiveness of regions and states. In analyzing national and European research on economic development, it is evident that the main criteria for assessing the competitiveness of a country are innovation and the factors that stimulate its development. It is widely acknowledged that organizational knowledge and effective knowledge management are the cornerstone of innovation in all types of organizations. Over the past 20 years, the public sector has undergone significant changes. A switch from the traditional bureaucratic approach to a more managerial one has been noticed. The activities of organizations in this sector are exceptionally knowledge-based; therefore, the application of knowledge management methods is a tool that organizations can promote innovation with to increase operational efficiency. This article, based on scientific literature, analyzes the importance of knowledge management for innovation within the public sector.